The impact of emotional labor and toxic leadership on workplace incivility: The moderating role of psychological capital - Nguyễn Thanh Hùng (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh)
This study explores the impact of emotional labor and toxic leadership on workplace incivility with the mediating role of emotional exhaustion and the moderating role of psychological capital. Using the Partial Least Square - Structural Equation Modeling (PLS-SEM) method to test data including 510 employees of logistics service companies in the Southeast region, the study discovered the mechanism of workplace incivility and the way to minimize it. Research results show that emotional labor and toxic leadership are predictors of workplace incivility, with emotional exhaustion as a mediating factor and psychological capital negatively moderating the relationships. Accordingly, the study proposes solutions for managers in assigning tasks and employees in managing emotions in logistics service companies to reduce negative emotions and workplace incivility at logistics companies through psychological capital. In addition, it helps to realize the importance of psychological capital in a context where the healing and positive energy of employees are indispensable to improve the logistics service companies’ performance.